Polypeptides of the surface projections and the ribonucleoprotein of avian infectious bronchitis virus. - Macnaughton, M R (1977)
Purified avian infectious bronchitis virus was digested with bromelain (0.7 mg/ml), and the surface projections were removed. Polyacrylamide gel electrophoresis of the polypeptides from these bromelain-treated particles showed that VP1, VP2, and VP5 were missing from the seven polypeptides. VP1 to VP7, that were present in untreated virus preparations. Milder bromelain treatment (0.07 mg/ml) left visible surface projections and polypeptides comprising VP1 and VP2 intact, but removed VP5. Thus, there are apparently two types of surface projections on the virus particle. The ribonucleoprotein complex was released from virus particles disrupted with 1% Nonidet P-40. The proportion of VP6 in such preparations was greatly reduced, implying that VP6 is the structural polypeptide of the ribonucleoprotein. Polypeptides VP1, VP2, VP4, and VP5 are glycosylated, but none of the polypeptides contains lipid.